Training Workshop on Plant Pest and Diseases and Risk Reporting Procedures Towards the Development of Ghana's Early Warning and Rapid Response System: Hands-on Training of Stakeholders - Dalaa, Mustapha Alasan; Tepa-Yotto, Ghislain; Ruber, Stella Esenam; Gariba, Awudu Amadu; Osae, Michael; Marri, Dinah (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
AICCRA Ghana Cluster led by the International Institute of Tropical Agriculture (IITA) together with PPRSD and BNARI organized a workshop and field training activity for monitoring and scouting technologies of the Early Warning and Rapid Response System (EWRRS) of pests, and component of Integrated Pest Management. The workshop was held on 18th and 19th of September 2023 at the Alisa Hotel, Accra, Ghana. The stakeholders present were; International Institute of Tropical Agriculture (IITA), Biotechnology and Nuclear Agriculture Research Institute (BNARI), Plant Protection and Regulatory Services Directorate (PPRSD-MOFA), University of Cape Coast, District Director of Agriculture-Cape Coast, District Director of Agriculture-Tuba, District Director of Agriculture-Wa, District Director of Agriculture-Okaikwei North, District Director of Agriculture -Tolon, Tuba farmers, Ghana Irrigation Development Authority (GIDA), RISKGEN Ghana, Director of the Department of Food and Agriculture-Cape Coast, and the Director of PPRSD.